Antimicrobial effect of coconut oil on Staphylococcus aureus: an implication of Staphylococcus epidermidis induced fermentation - Mahaklan, Lalita; Pratuangdejkul, Jaturong; Satitpatipan, Veena (Life Sciences, Medicine and Biomedicine, 2022)
Staphylococcus epidermidis is a commensal bacterium of human skin. S. epidermidis possesses lipolytic activity to digest skin surface lipids into the smallest unit of fatty acids (FAs). Most FAs hold antimicrobial properties essential for protecting skin from invading microorganisms. In this study, we were interested in virgin coconut oil (VCO), the source of several medium-chain fatty acids (MCFAs) such as lauric acid and caprylic acid. Those MCFAs products demonstrated remarkable antibacterial activity. Our results showed that crude supernatant from the culture medium of S. epidermidis with VCO fermentation exhibited the growth inhibition effect on Staphylococcus aureus. This bacterium causes a wide range of skin diseases. A co-culture of S. epidermidis and S. aureus in a rich medium with 2.5% (v/v) VCO significantly reduced the growth of S. aureus compared to those without VCO (p-value <0.05). Moreover, time-kill assays indicated that the supernatant from the culture medium of S. epidermidis with VCO fermentation showed an efficient antimicrobial activity against S. aureus after 18 hours of incubation. Our results concluded that the culture of S. epidermidis with VCO plausibly induced fermentation of natural lipid sources aiming the production of MCFAs with antibacterial activity, particularly suppression of skin pathogen S. aureus growth. The skin commensal bacterium S. epidermidis might help produce MCFAs from skin products containing VCO and make more benefits for skin infection protection.